2015
DOI: 10.1016/j.ccell.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Dehydrogenase 1 Signals through Antioxidant Glutathione Peroxidase 1 to Regulate Redox Homeostasis and Tumor Growth

Abstract: SUMMARY How mitochondrial glutaminolysis contributes to redox homeostasis in cancer cells remains unclear. Here we report that the mitochondrial enzyme glutamate dehydrogenase 1 (GDH1) is commonly upregulated in human cancers. GDH1 is important for redox homeostasis in cancer cells by controlling the intracellular levels of its product alpha-ketoglutarate (α-KG) and subsequent metabolite fumarate. Mechanistically, fumarate binds to and activates a ROS scavenging enzyme glutathione peroxidase 1 (GPx1). Targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
292
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(302 citation statements)
references
References 36 publications
9
292
0
1
Order By: Relevance
“…Studies have shown that glutamate dehydrogenase plays a key role in regulating redox homeostasis through the activation of GSH-Px [49]. In our study we found that STZ treatment significantly decreased the activity of GDH and increased ROS production, which might have activated the ROS scavenger enzyme, GSH-Px, to regulate the redox homeostasis.…”
Section: Discussionsupporting
confidence: 51%
“…Studies have shown that glutamate dehydrogenase plays a key role in regulating redox homeostasis through the activation of GSH-Px [49]. In our study we found that STZ treatment significantly decreased the activity of GDH and increased ROS production, which might have activated the ROS scavenger enzyme, GSH-Px, to regulate the redox homeostasis.…”
Section: Discussionsupporting
confidence: 51%
“…Although NQO1 knockdown potentiated anoikis in non-small cell cancer cells (33), manipulation of the levels of NCF2/p67PHOX, ALOX15, FAT4 and NQO1 produced no significant change in ROS in our cells (data not shown). GRHL2 also down-regulated Glutamate Dehydrogenase 1 (GDH1 or GLUD1), an enzyme implicated in the suppression of ROS (27). By western blotting, we found that GLUD1 protein was upregulated in MSP cells relative to HMLE cells, and downregulated in MSP by GRHL2 expression, in agreement with our RNA-seq data (figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Following deamination of glutamine to produce glutamate, glutamate dehydrogenase-1 (GLUD1 or GDH1) generates the Krebs cycle intermediate α-ketoglutarate (α-KG), which is converted by the Krebs cycle to fumarate, an important cofactor for glutathione peroxidase enzymes. Accordingly, α-KG is an important protective factor against oxidative stress, and GLUD1 is over-expressed in breast and lung carcinomas (26, 27). …”
Section: Introductionmentioning
confidence: 99%
“…GDH1 is upregulated in human cancers and important for redox homeostasis by controlling the intracellular levels of its product alpha-ketoglutarate and subsequent metabolite fumarate, which subsequently activates glutathione peroxidase 1, i.e., the antioxidant system. Targeting GDH1 by a small molecule inhibitor, the purpurin analog R162, resulted in an imbalanced redox homeostasis, which led to suppress tumor growth [193] . As described above, the common characteristics of glycolytic inhibitors were to increase ROS levels in cancer cells.…”
Section: Therapeutic Implications Of Targeting the Metabolic Interactmentioning
confidence: 99%